UJI BANDING KUALITAS CITRA RADIOGRAF SISTEM RADIOGRAFI DIGITAL MODIFIKASI TERHADAP COMPUTED RADIOGRAPHY SYSTEM DENGAN METODE CONTRASS TO NOISE RATIO - Muttaqin, Rodhotul; Susilo, Susilo (Universitas Negeri Semarang, 2017)
Modification of conventional radiography systems into a digital radiography system was conducted at the Laboratory of Physics Unnes. The image quality of digital radiography system that was developed in the Laboratory of Medical Physics Unnes need to be tested. The computed radiography (CR) system owned by Diponegoro National Hospital was chosen as a comparison with contrass to noise ratio (CNR) methode. Radiograph image generated by both radiography system then analyzed by software based on MATLAB. This study uses a copper plate phantom exposed to X-rays with a variation of anode-cathode voltage of 50 kV, 60 kV, 70 kV and 80 kV. For each voltage to vary the electrical current and expotion time of 1.6 mAs, 2.0 mAs, mAs 4.0, 8 mAs, 16 mAs and 32 mAs. Comparison of CNR for both systems to variations of tube voltage (kV) have a fixed value for the current and expotion time 4 mAs. Comparison of CNR for both systems to variations in current and ekspotion time (mAs) selected tube voltage 70kV.